IMPLEMENTASI PEMBELAJARAN BAHASA INDONESIA DALAM MENCERDASKAN KARAKTERISTIK SISWA - Udiatami, Dina Shofira; Arsanti, Meilan (Journal of Multidisciplinary Inquiry in Science, Technology and Educational Research, 2024)
This research aims to describe how to implement and develop Indonesian language learning in developing students’ characteristics. Learning Indonesian is one of the reasons why learning Indonesian must be taught at all levels of education, having goals that are no different from knowledge, skills, creativity and attitudes. This research will discuss how efforts to build and educate students’ character through implementing discipline and enforcing school regulations at the secondary school level is the right time to instill positive character traits in students which will become a blueprint for the rest of their lives, good character is one of the attitudes fundamental to how a person thinks and behaves.